Immunological responses following the third dose of the BNT162b2 SARS-CoV-2 vaccine among Japanese healthcare workers. Issue 11 (November 2022) - Tamura, Miku; Fujita, Retsu; Sato, Tomoaki; Sato, Ryohei; Kato, Yasuyuki; Nagasawa, Mitsuaki; Matsumoto, Tetsuya
Abstract: Introduction: A limited number of studies have shown a decline in antibody titers in healthcare workers beyond six months after the second dose of the BNT162b2 vaccine, and has been insufficiently investigated yet in the respective Asian ethnic groups. Methods: We conducted a longitudinal observational study on 187 healthcare workers and other personnel and healthy adults at least eight months after vaccination at the International University of Health and Welfare. Results: The baseline (before the third dose of BNT162b2) anti-receptor binding domain (RBD) IgG level was 569[377–943] AU/mL 245[240–250] days after the second dose. The mean antibody titer of participants aged 20–29 years was 4.6 times higher than that of participants aged 70–79 years. After booster vaccination, serum anti-RBD antibody levels were elevated in all participants with a median titer of 23, 250[14, 612–33, 401] AU/mL 21[19–23] days after the third dose. The median post-booster antibody titers in the 20–29, 30–39, 40–49, 50–59, 60–69, and 70–79 years age groups were 30.6, 33.0, 33.8, 27.4, 50.1, and 90.3 times, respectively, higher than the pre-booster ones. Antibody levels were 15% lower in daily drinkers compared to nondrinkers, suggesting that daily alcohol consumption can prevent antibody levels from increasing after vaccination. Our results show decreased antibody titers after two doses of the vaccine, especially in the elderly; however, the third dose of the vaccine resulted in a significant increase in antibody titers in all age groups. Conclusions: We provided information on antibody responses following primary and booster doses of the BNT162b2 mRNA COVID-19 vaccine in Japan.